1997
DOI: 10.1021/np9607013
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Activity of Phenolics from Pterocarpus marsupium

Abstract: Glucose levels in rats with hyperglycemia induced by streptozotocin were determined after i.p. administration of marsupsin (1), pterosupin (2), and pterostilbene (3), three important phenolic constituents of the heartwood of Pterocarpus marsupium. Marsupsin and pterostilbene significantly lowered the blood glucose level of hyperglycemic rats, and the effect was comparable to that of 1,1-dimethylbiguanide (metformin).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
151
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(157 citation statements)
references
References 16 publications
6
151
0
Order By: Relevance
“…We have been investigating the effects of phytochemicals on the prevention of cancer, using in vitro and ex vivo assay systems and have already reported that some food components, such as carotenoids, tea catechins, and resveratrol, have anti-proliferative and/or anti-invasive properties on hepatoma cells (Kozuki et al 2000;Zhang et al 2000a;Kozuki et al 2001). Pterostilbene (trans-3,5-dimethoxy-4 0 -hydroxystilbene) is a naturally occurring stilbenoid compound isolated from several natural plant sources including several types of grapes (Adrian et al 2000), blueberries (Rimando et al 2002), and the stem bark of several trees used in folk medicine such as Pterocarpus marsupium (Manickam et al 1997) and Guibourtia tessmanii (Fuendjiep et al 2002). Pterostilbene is an analogue of a well-studied stilbene, resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…We have been investigating the effects of phytochemicals on the prevention of cancer, using in vitro and ex vivo assay systems and have already reported that some food components, such as carotenoids, tea catechins, and resveratrol, have anti-proliferative and/or anti-invasive properties on hepatoma cells (Kozuki et al 2000;Zhang et al 2000a;Kozuki et al 2001). Pterostilbene (trans-3,5-dimethoxy-4 0 -hydroxystilbene) is a naturally occurring stilbenoid compound isolated from several natural plant sources including several types of grapes (Adrian et al 2000), blueberries (Rimando et al 2002), and the stem bark of several trees used in folk medicine such as Pterocarpus marsupium (Manickam et al 1997) and Guibourtia tessmanii (Fuendjiep et al 2002). Pterostilbene is an analogue of a well-studied stilbene, resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…Pterostilbene (3,5-dimethoxy-4#-hydroxy-trans-stilbene) was first isolated from red sandalwood (Pterocarpus santalinus; Seshadri, 1972) and is one of the active constituents of Pterocarpus marsupium, which is used in traditional medicine for the treatment of diabetes. Indeed, pterostilbene was found to decrease significantly plasma Glc levels in hyperglycemic rats (Manickam et al, 1997). Pterostilbene has also been reported to have hypolipidemic properties comparable to clinically used fibrate lipid-lowering drugs (Rimando et al, 2005).…”
mentioning
confidence: 98%
“…[12][13][14] When anti-diabetic effects of Vijaysar was compared with Glimepiride in present study, only 2h PG glucose was comparable to Glimepiride, while previous studies mentioned that all parameters of Vijaysar group was comparable to Tolbutamide, Glibenclamide, and Metformin. 5,[15][16][17] Vijaysar also decreases the plasma level of HbA1c which suggest long term effects (3 months) on blood glucose. Various studies had shown that Vijaysar exerts multiple effects on glucose metabolism and lipid metabolism which are responsible for its anti-diabetic effects and prevent deleterious effect of diabetes on various organs.…”
Section: Discussionmentioning
confidence: 99%